Analyzing the impact of ethnic identity on phonological variation: A case study of the Tamil community in Japan - Shen, Zijun; Zhao, Mingting (Universitas Dian Nuswantoro, 2024)
This completely delves into the tricky relationship between ethnic identification and phonological version inside the Tamil neighborhood in Japan. The Japanese Tamil community, like many diasporic communities, faces the task of preserving its ethnic identification and linguistic heritage in a multicultural context. In this multicultural Japanese society, the place where several languages and cultures intersect, this teaches about objectives to shed light on how the renovation of ethnic identification influences the phonological patterns of Tamil speakers. Drawing upon set-up sociolinguistic theories, this study seeks to unravel the multifaceted dynamics at play. Language version is now not a random occurrence; it is systematic and regularly associated with sociocultural factors. By focusing on the phonological aspects, this explores how the Tamil neighborhood navigates linguistic variety while keeping its ethnic identity.The research employs a detailed case study approach, allowing for an in-depth analysis of the phonological variations. Through interviews, recordings, and linguistic diaries, the study captures the natural speech patterns of Tamil speakers in Japan, providing valuable insights into how they adapt their language in this multicultural environment. The findings of this study are anticipated to be twofold. Firstly, they will enrich our understanding of language variation, especially within the context of diasporic communities. The nuanced phonological editions uncovered will furnish precious facts for linguists and sociolinguists fascinated by the complexities of language use in multicultural settings. Secondly, this study will shed light on the elaborate interaction between language, ethnicity, and identification in numerous sociolinguistic contexts like Japan. The adaptability of the Tamil neighborhood in negotiating their linguistic identification while accommodating linguistic variety can serve as a mannequin for different ethnic communities in various societies. Ultimately, this finds out about seeks to discover the profound effect of sociolinguistic elements on the maintenance of ethnic identity. It contributes to our broader grasp of language's position as an automobile for cultural upkeep and expression of identification in the world tapestry of multicultural societies.